(untitled) (Research Nepal Journal of Development Studies, 2024)
This article explains how the existence of Nepalese peasants shifted from being bound in coercive labor systems like Kamaiya, Haliya, Haruwa-Charuwa and Kamlari to working within a relatively more open, market oriented economy. Although Nepal has passed landmark legislation such as the Kamaiya Labour (Prohibition) Act, 2002, and constitutional guarantees against bonded labour under the September 20, 2015, promulgated Constitution of Nepal, discrimination grounded in caste, gender, and class remains an ongoing obstacle to transformative change at the local level. This study uses simple descriptive methods and past studies to follow the course of labor in Nepal from the 7th century up to the current times. The study indicates that despite the fact that many workers were legally freed, most of them have not been able to obtain land, labor as well as basic rights. Many others still do not have identity documents, earn dangerous and insecure livelihoods and also migrate to foreign countries under unsafe conditions. The research also shows that poor land reforms and over reliance on foreign labor and remittances have worked in favor of some more than others especially leaving out the most vulnerable groups. The report argues that in order for Nepal to successfully overcome forced labor, it has to prioritize equal distribution of land, good law enforcement, end discrimination and foster agriculture resilient to climate change. It suggests that policies to be based on human rights and offer rural people access to land, legal identity, vocational training and safe, secured and decent work.